2010
DOI: 10.1071/rd09078
|View full text |Cite
|
Sign up to set email alerts
|

Antiperoxidative and anti-apoptotic effects of lycopene and ellagic acid on cyclophosphamide-induced testicular lipid peroxidation and apoptosis

Abstract: The present study was conducted to investigate the possible protective effects of lycopene (LC) and ellagic acid (EA) on cyclophosphamide (CP)-induced testicular and spermatozoal toxicity associated with the oxidative stress and apoptosis in male rats. Forty-eight healthy adult male Sprague-Dawley rats were divided into six groups of eight rats each. The control group was treated with placebo; the LC, EA and CP groups were given LC (10 mg kg(-1)), EA (2 mg kg(-1)) and CP (15 mg kg(-1)), respectively, alone; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
67
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 47 publications
8
67
1
2
Order By: Relevance
“…EA is a naturally occurring plant polyphenol (Soong and Barlow 2004) that exhibits antioxidative properties both in vivo (Hassoun et al 1997) and in vitro (Seeram et al 2005). EA has wide array of biological properties, ranging from radical scavenging, to chemopreventive (Atessahin et al 2006;Turk et al 2008) and antiapoptotic properties (Turk et al 2010). The antioxidant effects of EA on cytotoxicity have been evaluated by different studies.…”
Section: Discussionmentioning
confidence: 99%
“…EA is a naturally occurring plant polyphenol (Soong and Barlow 2004) that exhibits antioxidative properties both in vivo (Hassoun et al 1997) and in vitro (Seeram et al 2005). EA has wide array of biological properties, ranging from radical scavenging, to chemopreventive (Atessahin et al 2006;Turk et al 2008) and antiapoptotic properties (Turk et al 2010). The antioxidant effects of EA on cytotoxicity have been evaluated by different studies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dietary intake of tomato and tomato-derived products can reduce the risks of chronic diseases and various cancers, especially prostate cancer (8,9) . Lycopene is a potent antioxidant as well as an inhibitor of proinflammatory and prothrombotic factors (10) , although the mechanisms for these additional activities have not been clarified. Lycopene was shown to inhibit formation of proinflammatory cytokines and chemokines in macrophages (11,12) .…”
Section: Introductionmentioning
confidence: 99%
“…Biological Sciences Maringá, v. 35, n. 1, p. 105-113, Jan.-Mar., 2013 SELVAKUMAR et al, 2006;TURK et al, 2010). CP toxic effects on testis were mainly attributed to oxidative stress on seminiferous tubules and Sertoli cells, impairing spermatogenis and androgenesis, and inducing germinal cells apoptosis (ILBEY et al, 2009;MOTAWI et al, 2010;REZVANFAR et al, 2008;TURK et al, 2010).…”
Section: Introductionmentioning
confidence: 99%